2003
DOI: 10.1046/j.1365-2044.2003.03410.x
|View full text |Cite
|
Sign up to set email alerts
|

Consent and anaesthetic risk

Abstract: SummaryThe incidences of mortality and morbidity associated with anaesthesia were reviewed. Most of the published incidences for common complications of anaesthesia vary considerably. Where possible, a realistic estimate of the incidence of each morbidity has been made, based on the best available data. Perception of risk and communication of anaesthetic risk to patients are discussed. The incidences of anaesthetic complications are compared with the relative risks of everyday events, using a community cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(32 citation statements)
references
References 237 publications
(246 reference statements)
1
29
0
1
Order By: Relevance
“…In the same study, 31 patients (0.08%) had major morbidity including myocardial infarction, central nervous system deficit, pulmonary embolism, and respiratory failure. In their recent work, Jenkins and Barker [13] demonstrated similar low mortality rate, 0.5 per 10 000 anesthetics.…”
Section: Qualitymentioning
confidence: 65%
“…In the same study, 31 patients (0.08%) had major morbidity including myocardial infarction, central nervous system deficit, pulmonary embolism, and respiratory failure. In their recent work, Jenkins and Barker [13] demonstrated similar low mortality rate, 0.5 per 10 000 anesthetics.…”
Section: Qualitymentioning
confidence: 65%
“…1, 2 Occurring as often as 1 in every 2–3,000 operations requiring anesthesia, 3 almost half of all patients who aspirate during surgery develop a related lung-injury, such as pneumonitis or aspiration pneumonia. 4 This issue is of particular relevance to thoracic surgeons; Sakai and colleagues retrospectively compared characteristics of patients with and without anesthetic-related pulmonary aspiration and found that aspiration occurred three times more often in thoracic surgical procedures than any other specialty.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the medical providers' concern that such information could instill anxiety in patients. In this regard, Jenkins and Baker claimed that, in the current medicolegal climate, patients should rarely have detailed information about the risks of anesthesia or surgery withheld on the grounds that they are likely to suffer adversely from such information [6]. Waisel and Truog suggested that the patient should determine the level chosen after initial statements about the more common risks [1].…”
Section: Discussionmentioning
confidence: 98%